The Role of Sufism in Overcoming the Problems of Modern Society - Taabudilah, Moch. Hilman; Maemun, Abdullah Rafi (STAI Darussalam Kunir, 2025)
The rapid growth and rotation of globalization in life has a significant impact on various aspects such as shifts in lifestyle patterns and lifestyles of today's society where moral and ethical principles are starting to be abandoned because they are considered incompatible with modern values. The purpose of this study is to analyze the role of Sufism in overcoming the problems of modern society. This study uses a qualitative research methodology through a literature review of primary and secondary sources relevant to this theme. The results of this study indicate that by applying Sufi principles to everyday life will have an impact on peace of mind by prioritizing the commands of Allah SWT over the lust for love of the world. Because Sufism in essence seeks to guide humanity towards a deeper closeness to Allah SWT. Sufism is very important for modern society because it can serve as a reminder for humans not to run away from their nature, thus making them more humane.